Thermohaline properties in the Eastern Mediterranean in the last three decades: is the basin returning to the pre-EMT situation? - V. Cardin; G. Civitarese; D. Hainbucher; M. Bensi; A. Rubino (Ocean Science, 2015)
Temperature, salinity and oxygen data collected during April and June 2011 (M84/3 and P414 cruises respectively) are analysed to derive the oceanographic characteristics of the Eastern Mediterranean (EM) basin. These observed characteristics are compared with those from previous cruises over the period 1987–2011. As a result, the interannual and decadal variability of the EM thermohaline properties are discussed in the context of the evolution of the Eastern Mediterranean Transient (EMT) and of the general circulation of the basin. We found that the state of the EM is still far from the pre-EMT conditions, though the 2011 results possibly indicate a slow return to this status. In particular, a comparison between thermohaline property evolution deriving from interannual variability of the preconditioning and air–sea interaction (heat fluxes) in the South Adriatic and the Cretan Seas reveals aspects of the alternation of the two dense water sources (Adriatic and Aegean) during the last three decades, which have strong implications for the hydrographic characteristics of the intermediate and deep layers of the Ionian and Levantine basins.